Dinamika Sebaran Bakteri Heterotrofik di Teluk Jakarta - Flandrianto Sih Palimirmo; Ario Damar; Hefni Effendi (Institut Pertanian Bogor, 2016)
Jakarta Bay is one of the aquatic ecosystems with the highest level of organic pollution in the world. Ecological condition of Jakarta Bay’s water will affect the ecosystem, including the distribution of heterotrophic bacteria. This study aims to determine the dynamics of the distribution of heterotrophic bacteria in the Jakarta Bay. Sampling was done by 4 repetitions during the year of 2013. Primary and secondary data was used in this research. The results showed an abundance of heterotrophic bacteria fluctuate and are relatively high in the area close to the mouth of the river and decreasing abundance in the ocean. The highest abundance obtained at Station 10 with 3,5 × 106 CFU/ml density and the lowest abundance obtained at Station 1 with 1,8 × 105 CFU/ml density. The highest density obtained in October with an average of 1,3 × 106 CFU/ml and the lowest density obtained in July with the average of 3,5 x 105 CFU/ml. Abundance of heterotrophic bacteria have a close relationship with chlorophyll-a